2019
DOI: 10.1101/cshperspect.a036087
|View full text |Cite
|
Sign up to set email alerts
|

PTEN in Hereditary and Sporadic Cancer

Abstract: Germline pathogenic phosphatase and tensin homolog (PTEN) mutations cause PTEN hamartoma tumor syndrome (PHTS), characterized by various benign and malignant tumors of the thyroid, breast, endometrium, and other organs. Patients with PHTS may present with other clinical features such as macrocephaly, intestinal polyposis, cognitive changes, and pathognomonic skin changes. Clinically, deregulation of PTEN function is implicated in other human diseases in addition to many types of human cancer. PTEN is an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 145 publications
0
31
0
Order By: Relevance
“…PTEN is an important phosphatase that plays a role in the interweaving of genetics and epigenetic regulation. PTEN dephosphorylates PtdIns(3,4,5)P 3 to form PtdIns(4,5)P 2 to negatively regulate PI3K/AKT signaling and has been shown to be related to the incidence of breast cancer and tumor progression (34,35), Consistent with previous research data, TNBC is rich in PTEN mutations and PTEN exhibits low expression at the transcriptome level and is related to treatment resistance and poor survival (36). FAT3, MUC16, and SYNE1 have also been mentioned as common mutant genes in breast cancer in previous studies, but there is no specific report on whether they affect the development and prognosis of breast cancer (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is an important phosphatase that plays a role in the interweaving of genetics and epigenetic regulation. PTEN dephosphorylates PtdIns(3,4,5)P 3 to form PtdIns(4,5)P 2 to negatively regulate PI3K/AKT signaling and has been shown to be related to the incidence of breast cancer and tumor progression (34,35), Consistent with previous research data, TNBC is rich in PTEN mutations and PTEN exhibits low expression at the transcriptome level and is related to treatment resistance and poor survival (36). FAT3, MUC16, and SYNE1 have also been mentioned as common mutant genes in breast cancer in previous studies, but there is no specific report on whether they affect the development and prognosis of breast cancer (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…These findings documented that PTEN is mutated in glioblastoma but not lower grade astrocytomas (Wang et al 1997;Duerret al 1998), prostate carcinoma (Wang et al 1998), breast cancer (Bose et al 1998), and endometrial carcinoma (Tashiro et al 1997). Mutation of PTEN was also documented in other human malignancies including lymphoma and cancer of the bladder, head and neck, ovary, thyroid, and gastrointestinal system but at lower frequency (see Ngeow and Eng 2019).…”
Section: Tumor Suppressor Gene On Chromosome 10mentioning
confidence: 99%
“…This was soon followed by a linkage analysis study that determined that the hereditary cancer predisposition syndrome known as Cowden disease (or syndrome) was linked to chromosome 10q22-23 (Nelen et al 1996), a segment contained within a previously implicated region found in tumor LOH studies. Cowden syndrome is associated with increased risk for the development of benign neoplasms known as hamartomas, but also cancer, including cancers of the breast and thyroid (see Ngeow and Eng 2019).…”
Section: Tumor Suppressor Gene On Chromosome 10mentioning
confidence: 99%
“…prosurvival PI3K/AKT pathway and downregulating cell growth, invasion, and migration (Lee et al, 2018;Milella et al, 2015;Ngeow & Eng, 2020;Pulido, 2015;Worby & Dixon, 2014). Many PTEN mutations associated with cancer confer loss of PTEN phosphatase activity or destabilization of PTEN protein (Andrés-Pons et al, 2007;Georgescu et al, 2000;Han et al, 2000;Rodríguez-Escudero et al, 2011;Spinelli et al, 2015).…”
mentioning
confidence: 99%